2012
DOI: 10.1002/bit.24443
|View full text |Cite
|
Sign up to set email alerts
|

The granule size distribution in an anammox‐based granular sludge reactor affects the conversion—Implications for modeling

Abstract: Mathematical models are useful tools to optimize the performance of granular sludge reactors. In these models, typically a uniform granule size is assumed for the whole reactor, even though in reality the granules follow a size distribution and the granule size as such affects the process performance. This study assesses the effect of the granule size distribution on the performance of a granular sludge reactor in which autotrophic nitrogen removal is realized through one-stage partial nitritation-anammox. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 62 publications
2
53
0
Order By: Relevance
“…In continuous reactors on the other hand, the microbial groups need to be separated in space, with anammox bacteria residing in anoxic zones of the microbial aggregates, provided by the oxygen demanding activities of AOB. In microbial granules, distinct patterns of stratification have been predicted by modelling and observed with microbiological methods, with AOB being located in the outer aerobic zone near the water interface and with anammox bacteria in the inner anoxic parts [48]. For nitritation-anammox biofilms on fixed substrata, the observed localization of microorganisms has been less straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…In continuous reactors on the other hand, the microbial groups need to be separated in space, with anammox bacteria residing in anoxic zones of the microbial aggregates, provided by the oxygen demanding activities of AOB. In microbial granules, distinct patterns of stratification have been predicted by modelling and observed with microbiological methods, with AOB being located in the outer aerobic zone near the water interface and with anammox bacteria in the inner anoxic parts [48]. For nitritation-anammox biofilms on fixed substrata, the observed localization of microorganisms has been less straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the Winkler et al remarked on the dominance in the floccular fraction of both reactors of AOO via FISH analyses. Volcke et al (2012) assessed the influence of a non-uniform granule size distribution on granular nitritation-anammox reactor macroscale and microscale characteristics, and concluded that size distribution influences microscale solute transport due to increased relative abundance of AOO in smaller granules and AMO in larger granules. Interestingly, our model indicated a similar segregation of microbial populations and activities due to the inclusion of a second biomass fraction without mass transport limitations (flocs), with AMO concentrated in (uniform size distribution) granules and AOO predominating in floccular biomass.…”
Section: Resultsmentioning
confidence: 99%
“…different microbial consortia at different locations in the agglomerate), the simulation of such a microenvironment within a macro-scale fluid transport environment has hardly been performed. Recently, Volcke et al (2012) demonstrated the significant impact of granule size distribution on the performance of an Anammox-based granular sludge reactor. The authors used a fixed size distribution for this analysis.…”
Section: Floc and Granule Size: Distributed Kineticsmentioning
confidence: 99%
“…The operational variables include aeration, mixing and flow rate, which if not optimally chosen can lead to bioreactor failure 8 . Mathematical models can be valuable tools to assist in the operation and control of these bioreactors, to enrich microbial composition in the right type of microbes 9 .…”
Section: Mathematical Models In Environmental Biotechnologymentioning
confidence: 99%